2000
DOI: 10.1080/14634980008650687
|View full text |Cite
|
Sign up to set email alerts
|

Metals in the sediments of Jauá Lake (Camaçari, Bahia, Brazil) following an episode of industrial contamination

Abstract: The contamination of sediments caused by the deposition of industrial residues from titanium dioxide production, in sand dunes near a wetland was assessed through atomic absorption spectrometry. The contamination occurred near a shallow freshwater wetland called Jauá Lake, along the coast of Camaçari, Bahia, Brazil. Five core samples were collected, including a reference site, from Jauá Lake and one from a small lake, near the deposition site. Cores were cut in 20-cm sections. Fractions <63 μm were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
0
12
0
3
Order By: Relevance
“…No Brasil, as determinações de elementos--traço em solos já têm sido realizadas por diversos autores (CAMPOS et al, 2003;COTTA et al, 2006;FADIGAS et al, 2006;MARQUES et al, 2002;PIERANGELI et al, 2001;REZENDE, 2009;SILVA et al, 2000;REZENDE, 2002;TOMAZELLI, 2003). Guilherme et al (2005) apresentam uma ampla revisão sobre elementos--traço em solos, sedimentos e água, considerando desde sua ocorrência natural e antropogênica até os seus efeitos deletérios e fatores que afetam sua dinâmica no ambiente.…”
Section: Revisão Bibliográficaunclassified
“…No Brasil, as determinações de elementos--traço em solos já têm sido realizadas por diversos autores (CAMPOS et al, 2003;COTTA et al, 2006;FADIGAS et al, 2006;MARQUES et al, 2002;PIERANGELI et al, 2001;REZENDE, 2009;SILVA et al, 2000;REZENDE, 2002;TOMAZELLI, 2003). Guilherme et al (2005) apresentam uma ampla revisão sobre elementos--traço em solos, sedimentos e água, considerando desde sua ocorrência natural e antropogênica até os seus efeitos deletérios e fatores que afetam sua dinâmica no ambiente.…”
Section: Revisão Bibliográficaunclassified
“…The literature review identified one study evaluating concentrations of titanium dioxide in sediments and mussels near a titanium dioxide production facility (da Silva et at. 2000).…”
Section: Bioaccumulation and Trophic Transfermentioning
confidence: 99%
“…Os metais podem ser introduzidos nos ambientes aquáticos nas formas: solúveis e particulados, estando sua distribuição sujeita a processos físico-químicos, hidrológicos e biológicos (Silva et al, 2000). A presença dos metais pesados nos sedimentos está associada às formações litogênicas, aos produtos de precipitação, às formações biogênicas, às fontes atmosféricas, às partículas extraterrestres e às fontes antropogênicas (Forstner e Wittman, 1981).…”
unclassified